2006
DOI: 10.1016/j.expneurol.2005.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Selective temporal and regional alterations of Nogo-A and small proline-rich repeat protein 1A (SPRR1A) but not Nogo-66 receptor (NgR) occur following traumatic brain injury in the rat

Abstract: Axons show a poor regenerative capacity following traumatic central nervous system (CNS) injury, partly due to the expression of inhibitors of axonal outgrowth, of which Nogo-A is considered the most important. We evaluated the acute expression of Nogo-A, the Nogo-66 receptor (NgR) and the novel small proline-rich repeat protein 1A (SPRR1A, previously undetected in brain), following experimental lateral fluid percussion (FP) brain injury in rats. Immunofluorescence with antibodies against Nogo-A, NgR and SPRR1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
0
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 112 publications
2
31
0
3
Order By: Relevance
“…In human, increased immunoreactivity of NogoA-positive hippocampal neurons was observed in Alzheimer disease [9] and temporal lobe epilepsy [3]. The increase was also present in the experimental models of brain diseases including epilepsy [28,41] or brain injury [26,28,30].…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…In human, increased immunoreactivity of NogoA-positive hippocampal neurons was observed in Alzheimer disease [9] and temporal lobe epilepsy [3]. The increase was also present in the experimental models of brain diseases including epilepsy [28,41] or brain injury [26,28,30].…”
Section: Introductionmentioning
confidence: 70%
“…In the fluid percussion model of traumatic brain injury applied to frontoparietal cortex, numerous NogoA-ir neurons were observed in the hilus of the dentate gyrus of sham-injured rats. These neurons in the ipsilateral HDG were found to be selectively vulnerable to injury and their number was decreased 7 days after injury [26]. Unfortunately, analysis of contralateral hippocampus was performed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that the neuronal content of Nogo-A was increased in RGC neurons after optic nerve injury, similar to results recently described for cortical and thalamic neurons after stroke. 13,14 This opens the possibility that neuronal Nogo-A may have a role in the cell death/survival and/or regeneration response of injured CNS neurons. 14 Interestingly, the genetic deletion of Nogo-A/B in mutant mice worsened the motor and cognitive deficits after traumatic brain injury and accelerated the degeneration of motorneuron axons in a model of amyotrophic lateral sclerosis (ALS).…”
mentioning
confidence: 99%
“…13,14 This opens the possibility that neuronal Nogo-A may have a role in the cell death/survival and/or regeneration response of injured CNS neurons. 14 Interestingly, the genetic deletion of Nogo-A/B in mutant mice worsened the motor and cognitive deficits after traumatic brain injury and accelerated the degeneration of motorneuron axons in a model of amyotrophic lateral sclerosis (ALS). [14][15][16] A neuroprotective effect of Nogo was proposed to be related to an attenuation of endoplasmic reticulum (ER) stress.…”
mentioning
confidence: 99%
See 1 more Smart Citation